1989
DOI: 10.1007/bf00202399
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a thermo-osmotic gas transport mechanism in Alnus glutinosa (L.) Gaertn.

Abstract: Summary. A gas transport system based upon the physico-chemical effect of thermo-osmosis of gases in described for the black alder, Alnus glutinosa (L.) Gaertn. Air is transported through the alder's stem to the roots, thus improving 02 supply to respiring tissues of the root system. The gas transport system is investigated by means of a tracer gas technique (I 1% ethane in air, v/v). Gas transport depends on any source of radiant heat generating a temperature difference between the tree's stems and the atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…5 is only valid for lowland rice varieties because gas transport mechanisms differ among plants. Aquatic plants such as the waterlily Nuphar Iuteurn (Dacey 198 I), cattail Typha latifolia (Sebacher et al 1985) or some trees Alnus glutinosa (L.) (Schroder 1989) possess an active thermally driven ventilation system that largely controls gas transport in these plants. Such a ventilation system is absent in rice Oryza sativa (Chanton & Dacey 1992).…”
Section: Resultsmentioning
confidence: 99%
“…5 is only valid for lowland rice varieties because gas transport mechanisms differ among plants. Aquatic plants such as the waterlily Nuphar Iuteurn (Dacey 198 I), cattail Typha latifolia (Sebacher et al 1985) or some trees Alnus glutinosa (L.) (Schroder 1989) possess an active thermally driven ventilation system that largely controls gas transport in these plants. Such a ventilation system is absent in rice Oryza sativa (Chanton & Dacey 1992).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the outstanding success of black alder at water logged and temporarily flooded sites, where low oxygen supply in the soil excludes other trees, is due to specific morphological and structural changes in response to flooding. These changes include the emergence of adventitious roots (Gill 1975), the formation of hypertrophied lenticels at the stem base, the development of aerenchyma tissue and a gas transport system based upon the physico-chemical effect of thermo-osmosis (Schröder 1989). Continuously high transpiration rates could be beneficial to productivity not only because the high leaf conductances allow greater CO 2 uptake, but also because mass flow towards the roots would provide a good nutrient supply even at poor sites.…”
Section: Discussionmentioning
confidence: 99%
“…In A. glutinosa and A. incana the respiratory oxygen demand of the roots was covered completely by the pressurized gas transport and excess oxygen was excreted into the rhizosphere (SchrOder 1986(SchrOder , 1989Grosse et al 1990). The improved oxygen supply to the roots was beneficial to the wetland trees not only by increasing the adenosine triphosphate (ATP) level and .the plants' subsequent vigor, but also by elevating the roots' superoxide dismutase (SOD) activity to a higher level (Grosse et al 1993), which is suggested to protect some monocots from postanoxic injury following periods of soil anoxia and flooding .…”
Section: Introductionmentioning
confidence: 99%